Influência do consumo crônico de diferentes concentrações de álcool nos tecidos periodontais e na evolução da periodontite experimental - Cabrera Pazmiño, Victor Fabrizio [UNESP] (2015)
Aim: The aim of this study was to evaluate the influence of chronic intake of different alcohol concentrations on periodontal tissues and the evolution of experimental periodontitis (EP). One hundred sixty male rats were set into four experimental groups: GROUP EP-NT: normal rats with EP; GROUP EP-A14° (n=40): rats with EP exposed to alcohol with 14% concentration; GROUP EP-A25 (n=40): rats with EP exposed to alcohol with 25% concentration; GROUP Ep-A36% (n=40) rats: rats with EP exposed to alcohol with 36% concentration. The animals from groups EP-A14°, EP-A25° and EP-A36° were subjected to each respective alcohol concentration 30 days before the ligature placement. Blood samples were collected before beginning the administration of the alcoholic solutions in all experimental periods. Ten animals from each group were euthanized at 3, 7, 15 and 30 days after EP induction. Were obtained semi-serial sections with 4m thickness in mesio-distal direction and stained with hematoxylin-eosin or Masson Trichrome. The percentage of bone in the furcation area (PBF) was evaluated by histomorphometric analysis, and were realized histological, immunohistochemical and biochemical analyzes. The histological, histometrical and immuhistochemical analyzes showed that on EP-NT group the ligature was able to induce alveolar bone loss (p<0,05). On groups EP-NT, EP-A14, EP-A25 and EP-A36 the alcohol exacerbated the alveolar bone loss at each experimental periods (p<0,05). The biochemical analysis showed decreased levels of alkaline phosphatase (AP) in all experimental groups after EP when compared to the baseline of each experimental group. In ALT and AST analyzes, was observed that these markers expressed a significant increase in all experimental groups after EP when compared to each respective baselines. Within...